Superalloys 2012 (Twelfth International Symposium) 2012
DOI: 10.7449/2012/superalloys_2012_615_624
|View full text |Cite
|
Sign up to set email alerts
|

Dendrite Bending during Directional Solidification

Abstract: In order to ascertain the origin of deformation and sub-grains in single crystal castings, an in situ, time-resolved X-ray radiographic imaging experiment was performed at the BM05 beam line of the European Synchrotron Radiation Facility (ESRF). This provided direct experimental evidence of the origin of crystallographic misorientation during the directional solidification of the nickel-based superalloy CMSX4. Solidification monitoring revealed that dendrites deform by bending and possibly torsion, and with de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…A good overview on crystal mosaicity in SX has been provided in reference [30]. Mosaicity is caused by the deformation of dendrites during solidification [37][38][39][40][41][42][43]. As each dendrite is expected to grow along its crystallographically preferred direction [44], the preparation of a perfect single crystal requires that all dendrites grow exactly parallel.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A good overview on crystal mosaicity in SX has been provided in reference [30]. Mosaicity is caused by the deformation of dendrites during solidification [37][38][39][40][41][42][43]. As each dendrite is expected to grow along its crystallographically preferred direction [44], the preparation of a perfect single crystal requires that all dendrites grow exactly parallel.…”
Section: Introductionmentioning
confidence: 99%
“…Dendrite deformation results in small crystal lattice rotations and thus in non-parallel growth, which gives rise to mosaicity. Possible reasons for dendrite deformation have been discussed in [29,41,42,[45][46][47][48][49][50][51]. Doherty [29] suggested two categories of dendrite deformation processes, namely, morphological and mechanical bending.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, these methods elucidate little information regarding the influence of bulk variations in the solidification environment on resultant (001) misorientation 17 . Synchrotron topography studies have directly observed metallic deformation during solidification 18 , 19 . However, low X-ray penetration depth within metals has restricted investigation to samples with volumes orders of magnitude smaller than typical single crystal turbine blades.…”
Section: Introductionmentioning
confidence: 99%
“…Single crystal (SX) Ni-based superalloys are widely used as blade materials in advanced aeroengines and industrial gas turbines (IGTs) because of their excellent mechanical properties. However, when casting these SX components especially large-size IGT blades, there is a high probability of inducing LAGBs due to the intersection or distortion of primary dendrites during directional solidification [1,2]. An elastically distorted region is generated around LAGBs, and the resulting local strain field interacts with the moving dislocations during deformation, which may lead to premature damage.…”
Section: Introductionmentioning
confidence: 99%